THE ROLE OF THE DIRECTORATE OF TRAFFIC OF NORTH SUMATRA REGIONAL POLICE IN HANDLING TRAFFIC ACCIDENT PROBLEMS IN MEDAN CITY - Ahli Ridho Mangungsong (NOMOI Law Review, 2021)
Medan is the region with the highest population in North Sumatra province. This has an impact on the increasing needs of the population of Medan for education, economy, and others that encourage the increasing mobilization of the population. The rapid increase in the number of motor vehicles is based on the need to facilitate human activities. If you look at the traffic conditions in Medan city has not shown a better direction there are still many violations of motor vehicle traffic occurred. Police are law enforcement tools that can provide protection, protection, and prevent crimes in people's lives. The police have a role to play in regulating traffic, in order to minimize traffic accidents. A Traffic Accident is an incident on the road that does not suspect and unintentionally involve a Vehicle with or without another Road User resulting in human casualties and/or property losses. This research is descriptively analytical, which reveals the laws and regulations related to the theories of law that become the object of research. The form of method of this writing research is a method of normative juridical approach. The normative juridical approach method is in this study that is examined only library material or secondary data, which may include primier, secondary, and tertiary legal materials. The role of the Directorate of Traffic of the North Sumatra Regional Police in tackling the problem of traffic accidents specifically in the city of Medan conducts in two ways, namely preventive (prevention) and repressive (crackdown), and the obstacles encountered by the Directorate of Traffic Police North Sumatra is the Lack of Personnel Integrity, Budget Limitations, Facilities and Infrastructure, Legal Procedures, Lack of Cooperation With Other Agencies, and Public Awareness. The solution of the obstacles by the Directorate of Traffic of the North Sumatra Regional Police is to seek transparency and accountability, reinventing the Police organization, always maintaining and maintaining existing facilities and infrastructure, Strictly prohibiting the police to receive rewards and urging the public to comply with traffic signs.Keywords: Traffic, Accident, Medan.